Critical factors influencing inventory and procurement system of infrastructure projects - Al-Aidrous, Al-Hussein Mohammed Hassan; Hern, Ng Jenn; Rahmawati, Yani; Jahja, Mohamad; Yusof, Khamaruzaman Wan; Zawawi, Noor Amila Wan Abdullah; Utomo, Christiono; Raflis (Journal of Civil Engineering and Management, 2022)
The performance of any construction project is highly influenced by the efficient planning of materials among construction supply chain players. The improper planning for the construction project has been discussed recently in the literature, with a special focus on the logistic and material aspects. Completing a construction project within time and cost constraints is highly affected by the inventory management system. Such evidence proves the big impact of the inventory management system on construction performance. Derived from these arguments, the critical impact of the inventory and procurement system used at the construction site is definite. This research aims to examine the main factors that need to be considered when developing an inventory and procurement management system and classify the most influential and impactful factors. This research adopted a two-steps methodology, which started with an interview with construction experts then followed by a questionnaire survey targeting project managers and engineers from MRT Line 2 Tunneling infrastructure project in Malaysia. Exploratory Factor Analysis (EFA) was used for data analysis as well as the scatter plot of the mean and standard deviation analysis. The most critical factors affecting the inventory and procurement handling are related to the operation and management aspects. The top five impactful factors are communication between labor and management, information sharing, software usage on material tracking, purchasing plan, and construction progress. The research outcomes can be used to develop further mitigation plans in the early stages of infrastructure projects.